Transformation of the Bahuma Tradition: The Impact of Agri Cultural Modernization on Socioeconomic and Environmental Conditions in Banua Hanyar Village, Kertak Hanyar District - Muhammad Ridho; Annida Afifah; Radiana Rosada (JIS: Journal Islamic Studies, 2026)
The values of the Banjar community have changed as a result of the modernization of bahuma practices. The purpose of this research is to examine the consequences of the modernization of bahuma practices on social, economic, and environmental issues. The study took place in Banjar Regency's Kertak Hanyar District's Banua Hanyar Village. The descriptive qualitative method was used for data gathering through in-depth interviews with chosen informants. In order to increase the validity of the results in this investigation, supporting data was gathered. The study's findings indicate that factory and property owners gain financially from modernization. The decline in employed labor during the harvest season is a significant contributor to this rise in earnings. But because of the substitution of human labor, paid employees have a hard time making ends meet on a daily basis. Landowners suffer losses as a result of the environmental harm caused by the usage of machines and chemical fertilizers. The peatland surface area decreases significantly every year as a result of heavy machinery operations. The peat soil's structure is inadequate to bear the machines' massive load. The sustainability of the rice field ecosystem at the research location is seriously jeopardized by combine harvesters. Additionally, the fertility of agricultural land is adversely affected by the regular application of synthetic fertilizers. The dilemma between short-term economic efficiency and environmental sustainability is brought about by the modernization of agricultural methods. A sustainable technological strategy that considers the long-term well-being of the surrounding population is necessary.